2018
DOI: 10.1186/s12302-018-0172-y
|View full text |Cite
|
Sign up to set email alerts
|

(Persistent) Organic pollutants in Germany: results from a pilot study within the 2015 moss survey

Abstract: BackgroundSince 1990, every 5 years, moss sampling is conducted within the European moss monitoring programme to assess the atmospheric deposition of airborne pollutants. Besides many other countries, Germany takes regularly part at these evaluations. Within the European moss monitoring 2015, more than 400 moss samples across Germany were taken according to a harmonized methodology for the assessment heavy metal and nitrogen input. In a pilot programme, eight of these sites were chosen for additional investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It consists mainly of polyaromatic hydrocarbons and alkanes of low molecular weight PAHs and low molecular weight [2]. The fate of the former compounds generally is of great concern to human health, since they are toxic to plants and carcinogenic to humans [3]. Uncontrolled releases of these compounds into soil around power houses are common as a result of inefficient control practices [4].…”
Section: Introductionmentioning
confidence: 99%
“…It consists mainly of polyaromatic hydrocarbons and alkanes of low molecular weight PAHs and low molecular weight [2]. The fate of the former compounds generally is of great concern to human health, since they are toxic to plants and carcinogenic to humans [3]. Uncontrolled releases of these compounds into soil around power houses are common as a result of inefficient control practices [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a nationwide assessment of POPs in Germany, as part of the European Moss Survey initiatives in 2015, Dreyer et al ( 2018 ) analyzed 400 moss samples following a harmonized methodology. Results indicated that (i) mosses have appreciable bioaccumulation potential for a wide array of POPs (e.g., PAHs, PCBs, PCDD/Fs, HBCDs) and thus aid in monitoring atmospheric concentrations, and (ii) compared to nearby tree leaf samples, mosses have high accumulation potential for pollutants of high octanol–air partition coefficient (KOA) and octanol–water partition coefficient (KOW).…”
Section: Resultsmentioning
confidence: 99%
“…Also, other potential pollutants, such as nitrogen or persistent organic pollutants (POP), should be included. First pilot studies on POP exist, for example, in Germany [5].…”
Section: Discussionmentioning
confidence: 99%
“…Within the LRTAP convention, European Moss Survey (EMS) is conducted using naturally growing mosses as biomonitors of atmospheric deposition of air pollutants. Since 1990, moss specimens have been sampled every 5 years at up to 7300 sampling sites in up to 35 countries [2–4] to determine the concentrations of heavy metals (HM), nitrogen (N, since 2005) and persistent organic pollutants (POPs, since 2010) [4, 5]. The EMS is coordinated by the ICP Vegetation, an international cooperative programme (ICP) reporting on impacts of air pollution on vegetation to the LRTAP convention [3].…”
Section: Introductionmentioning
confidence: 99%